The USDA‐ARS Experimental Watershed Network: Evolution, Lessons Learned, Societal Benefits, and Moving Forward. Issue 2 (16th February 2021) - Goodrich, D. C.; Heilman, P.; Anderson, M.; Baffaut, C.; Bonta, J.; Bosch, D.; Bryant, R.; Cosh, M.; Endale, D.; Veith, T. L.; Havens, S. C.; Hedrick, A.; et al.
Abstract: The U.S. Department of Agriculture‐Agricultural Research Service's (ARS) Experimental Watershed Network grew from Dust Bowl era efforts of the Soil Conservation Service in the mid‐1930s with the establishment of small experimental watersheds. In the 1950s, five watershed research centers with intensively instrumented watersheds at the scale of 100 to 700 km 2 were established. Primary network research objectives were to quantify on‐site and downstream effects of conservation practices and develop rainfall‐runoff relationships for design of water conservation structures. With passage of the Clean Water Act in 1972, research objectives have evolved to add a variety of observations relevant to the water quality issues. Many of the watersheds within the network have served, and continue to serve, as core validation sites for satellite sensors. As a result of the network's long history and intensive monitoring, coupled with mission‐driven research, a deep knowledge base of watershed processes has been developed. This has led to the extensive development and validation of numerous watershed models that are in widespread use today. The visionary investments in building and maintaining this network and associated scientific investigations for more than half a century have not only resulted in numerous high‐impact research accomplishments but also a wide array of accomplishments that directly benefit society. The ARS Experimental Watersheds formed the core of the Conservation Effects Assessment Project (CEAP) as well as the recently established Long‐Term Agroecosystem Research (LTAR) network. LTAR will expand the mission of the ARS Watersheds Network to include agricultural intensification, maintaining or improving ecosystem services while enhancing rural prosperity. Plain Language Summary: Understanding how watersheds respond to precipitation, agricultural management, and other land use changes is critical to maintaining clean water, viable food production, and predicting flood hazards and soil loss from erosion. To understand watershed responses and processes, the Soil Conservation Service, followed by the USDA‐Agricultural Research Service, established experimental watersheds across the United States. These watersheds were instrumented with equipment to make detailed measurements of weather and watershed response. Experiments were designed to observe how runoff, erosion, and water quality might change with changing agricultural practices to change agricultural practices and observe how runoff, erosion, and water quality would change. From these experiments, predictive computer models were developed and tested with data from the watersheds. The watershed observations, the process knowledge developed, and associated research and models have resulted in numerous societal benefits. Billions of dollars of conservation measures and drainage infrastructure investment were guided by these models and methods. The ARS Experimental Watersheds formed the core of the recently established Long‐Term Agroecosystem Research (LTAR) network. LTAR will expand the mission of the ARS Watershed Network to include producing more food on the same amout of land, maintaining or improving ecosystem services (clean water and air, healthy soils, etc.) while enhancing rural prosperity. Key Points: Agricultural Research Service's Experimental Watersheds and associated mission‐driven research have operated for over half a century High‐resolution watershed observations and experimentation have produced a deep watershed process knowledge and database The research network has been critical to developing and validating numerous watershed models and management methods, resulting in extensive societal benefits